An action research study on keeping a writing journal to improve the eleventh grade students’ writing at a high school in Yen Bai province = Nghiên cứu cải tiến sư phạm về việc sử dụng nhật ký ghi chép để nâng cao khả năng viết của học sinh lớp - Nguyễn, Thị Hằng (2019)
This research is the investigation of the predominant problems in learning writing at a high school in Yenbai province and the implementation of new technique to deal with situation, which, in this case, is journal writing. The primary purpose of the study is an attempt to find out how to apply journal writing in teaching writing to the 11th grade students and to what extent the journal writing impacted on the students‟ attitudes and their writing performances.